2014
DOI: 10.1002/cbf.3069
|View full text |Cite
|
Sign up to set email alerts
|

Lefty inhibits in vitro decidualization by regulating P57 and cyclin D1 expressions

Abstract: Endometrial decidualization is highly important for successful construction and maintenance of embryo implantation and pregnancy. Lefty gene at different menstrual cycle phases has different expressions, indicating its regulatory significance. To study the mechanism of Lefty in decidualization, human endometrial stromal cells (hESCs) were cultured and induced with medroxyprogesterone acetate (MPA) and 8-bromoadenosine-cAMP (8-Br-cAMP) in vitro as a research model. Our results showed that Lefty1 overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“… 30 , 31 Data also show that Lefty-1 may regulate the cell cycle by modulating the expressions of P57 and cyclin D1 to inhibit the decidualization process. 32 As observed in the present study, Lefty-1 regulates the cell cycle, which may be an important part of its suppression of the activation and proliferation of TGF-β1-induced NRK-49F cells. Overall, the results indicate that Lefty-1 is a crucial mediator of activation of Smad3, JNK-3 and BMP-5, all of which are critical signaling molecules for fibroblast–myofibroblast transdifferentiation in response to TGF-β1.…”
Section: Discussionsupporting
confidence: 71%
“… 30 , 31 Data also show that Lefty-1 may regulate the cell cycle by modulating the expressions of P57 and cyclin D1 to inhibit the decidualization process. 32 As observed in the present study, Lefty-1 regulates the cell cycle, which may be an important part of its suppression of the activation and proliferation of TGF-β1-induced NRK-49F cells. Overall, the results indicate that Lefty-1 is a crucial mediator of activation of Smad3, JNK-3 and BMP-5, all of which are critical signaling molecules for fibroblast–myofibroblast transdifferentiation in response to TGF-β1.…”
Section: Discussionsupporting
confidence: 71%
“…Failure to down-regulate LEFTYA secretion during the mid-luteal phase of the cycle may lead to premature 'closure' of the uterine lumen via ENaC-mediated fluid absorption, resulting in implantation failure [20,39]. The present observations, however, do not provide insight into the purported inhibitory effects of LEFTYA on decidualization of the endometrial stroma [40,41]. A previous study reported that induction of ENaC activity in response to embryonic proteases promotes decidualization by depolarizing the cell membrane of epithelial cells, leading to activation of voltage gated Ca 2+ channels, induction of COX-2 in …”
Section: Discussioncontrasting
confidence: 51%
“…Consistent with the inhibitory role of LEFTY in uterine decidualization in mice, overexpression of LEFTY1 in human ESCs impairs their secretion of PRL and IGFBP1 [ 84 ]. Studies using human uterine fibroblast cells also support an inhibitory function of LEFTY in uterine decidualization, with the involvement of key transcription factors, FOXO1 and ETS proto-oncogene 1 (ETS1) [ 58 ].…”
Section: Tgfb Superfamily Signaling Regulates Uterine Decidualizationmentioning
confidence: 76%